Involvement of Paranasal Sinuses in Patients with Bilateral Nasal Polyps: A Cross-Sectional Descriptive Study at Swabi: Paranasal Sinuses in Patients with Bilateral Nasal Polyps - Badshah, Jawad; Khalilullah, .; Asadullah, .; Khan, Waseem; Abbas, Arshad; Nizam, Saira; Kakakhel, Syed Ihtisham (Pakistan Journal of Health Sciences, 2025)
Non-neoplastic, pedunculated swellings of the sinonasal mucosa are called sinonasal polyps. They are called polyposis when they occur in multiple numbers. Objectives: To determine the frequency of paranasal sinus involvement in patients with bilateral nasal polyps aged 20–50 years using a validated self-structured questionnaire and radiological imaging. Methods: A cross-sectional descriptive study was conducted at the ENT Department of Bacha Khan Medical Complex, Swabi, from January 24, 2024, to June 23, 2024. A sample size of 50 patients was selected using a convenient sampling technique. Data were collected using a pre-tested, validated questionnaire, and sinus involvement was assessed via CT scans. Descriptive statistics were analyzed using SPSS version 26.0. Results: Among 50 patients, 72% (n=36) were male, and 28% (n=14) were female. The 20–25 age group constituted 30% (n=15) of the sample. Maxillary sinus involvement was most common (36%), followed by ethmoid (26%), frontal (26%), and sphenoid sinuses (18%). Bilateral maxillary sinus involvement was observed in 40% of patients. Conclusions: It was concluded that the study highlights the predominant involvement of maxillary sinuses in bilateral nasal polyps, emphasizing the need for comprehensive radiological evaluation to guide management. The findings align with existing literature but underscore the need for larger, randomized studies to improve generalizability.